2020
DOI: 10.1021/acs.iecr.0c02534
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Damage and Its Relation to Surface Adsorption/Desorption of Rejuvenators

Abstract: This paper uses a multiscale approach to study the preferential surface adsorption of bio-based rejuvenators to siliceous substrates, used here as surrogates for mineral stones like quartz in bituminous composites. Bituminous composites are the main building blocks of asphalt pavements and roofing shingles. Various rejuvenators, including bio-based rejuvenators, are commonly used to extend the service life or facilitate the recycling of aged bituminous composites reclaimed at the end of their service life. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Absorbing the acid from bitumen can improve the moisture susceptibility of pavement. 39,40 ■ CONCLUSIONS Introduction of Winz promotes sustainability by enhancing pavements' durability via enhanced wax dispersion within the bitumen matrix and increased resistance to moisture damage by diverting acids from the interface of bitumen and stones. The study results can be summarized as follows: • SEM images confirmed that the nanozeolites were impregnated by paraffin waxes producing wax-impregnated nanozeolite referred to as Winz.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbing the acid from bitumen can improve the moisture susceptibility of pavement. 39,40 ■ CONCLUSIONS Introduction of Winz promotes sustainability by enhancing pavements' durability via enhanced wax dispersion within the bitumen matrix and increased resistance to moisture damage by diverting acids from the interface of bitumen and stones. The study results can be summarized as follows: • SEM images confirmed that the nanozeolites were impregnated by paraffin waxes producing wax-impregnated nanozeolite referred to as Winz.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This phenomenon results in the release of wax, which was shown in the results of experiments. Absorbing the acid from bitumen can improve the moisture susceptibility of pavement. , …”
Section: Resultsmentioning
confidence: 99%
“…It has been noticed that linoleic acid and hexadecenoic acid are water-insoluble fatty acids and can easily be absorbed effectively in dry conditions. Thus, in a wet environment, these fatty acids are immediately replaced by water molecules, which in turn raises moisture susceptibility [107,108]. It can be inferred from the summarized studies that WCO-modified asphalt mixtures may fulfil the specification criteria.…”
Section: The Impact Of Waste Cooking Oil On the Performance Of Asphalt Mixturesmentioning
confidence: 99%
“…18 We have recently shown that by controlling the composition of biomodifiers, the adsorption of biomodifiers to siliceous minerals in a wet environment can be increased, leading to enhanced resistance to moisture damage in revitalized aged asphalt. 19 In terms of modifier's composition, the biomodifiers with lower polarizability have shown better resistance to aging and moisture damage. 20 Studies show that the binders containing biomodifiers made from swine manure are less susceptible to both moisture and oxidative aging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is worth noting that DFT-based reactivity descriptors demonstrate the molecular level reactivity of the target species, while rheology-or energy-based reactivity descriptors work at the matrix level. In the energy-based case, a significant change in energy of the bitumen matrix after water exposure indicates that bitumen has a lower affinity for the select substrate than the water; as such water molecules are expected to replace bitumen molecules, which were originally adsorbed to the glass substrate; 33 this in turn indicates susceptibility of target bitumen to moisture damage.…”
Section: ■ Introductionmentioning
confidence: 99%